Productivity Loss and Misallocation of Resources in Southeast Asia - de Nicola, Francesca (The World Bank, 2020)
This paper examines within-sector resource misallocation in three Southeast Asian countries - Indonesia, Malaysia, and Vietnam. The methodology accounts for measurement error in revenues and costs. The firm-level evidence suggests that measurement error is substantial, resulting in an overestimation of misallocation by as much as 30 percent. Nevertheless, resource misallocation across firms within a sector remains large, albeit declining. The findings imply that there are considerable potential gains from efficient reallocation - above 80 percent for Indonesia and around 20 to 30 percent for Malaysia and Vietnam. Private domestic firms and firms with higher productivity appear to face larger distortions that prevent them from expanding